Choosing the best nutrition condittion for the bacteria Acetobacter xylinum D9 - Kim Nhung, Dinh Thi; Thuy Van, Nguyen Thi (Academia Journal of Biology, 2012)
Acetobacter xylinum is a gram-negative bacterium, which characteristically synthesizes bacterial cellulose (BC). It is used as artificial blood vessels for microsurgery. The extremely fine filament is used to produce a new type of artificial leather with a mild touch. Thank to its hydrophilicity, it is used temporarily as a skin substitute and in wound healing bandages. It is also being used for producing activated carbon fibre sheets for absorption of toxic gas. Our study aimed to examine some biological properties of strain A. xylinum D9; the optinum condition for this strain was determined at temperature 30oC; time 7 days; pH 5.0. Bacterial cellulose membrane obtained in white, odorless, valued in terms of sensory. It was also found that, the bacterial cellulose was a promising candidate for burn wound treatment.